Differential phenolic production of Vitis vinifera cell cultures induced by Phaeomoniella chlamydospora elicitation - Lima, M. R. M. (2004)
Esca is a destructive disease, of complex aetiology, that affects grapevines in several countries around the world, specially in the Mediterranean, South Africa and California (where is known as “black measles”). In the last few years the disease became a major concern given to its dramatic incidence increase. Till now, does not exist a method to treat plants attacked by Esca. To study the putative response of V. vinifera plants to Paeomoniella chlamydospora (Pc), a fungus directly related with Esca, we utilized in cells cultures of Vitis vinifera cv. Vinhão (Vv) elicited with fungi Pc autoclaved extracts and methyl jasmonate (MeJ).